IMPLEMENTASI SISTEM PAKAR METODE CERTAINTY FACTOR UNTUK MENDIAGNOSA KERUSAKAN VESPA CLASSIC - Sarif Surorejo; Nugroho Adhi Santoso; Moh. Jamaludin (Nusantara Hasana Journal, 2022)
The development of the automotive world is always faster. Lifestyle changes in Indonesia, especially motorbikes are a hobby of various circles. Old and young, not only high-tech motorbikes, but many like old or classic motorbikes that have many fans. One of them is Vespa motorbikes. system design is one of the important elements in research. The following system design techniques are used in accordance with the formulation of the problem using a classical or waterfall algorithm approach. From the results of the research conducted, some data on the symptoms of damage to the Vespa Classic are as follows. ) into the Expert System to diagnose damage to vespa classic. The conclusions generated in this study are as follows: Implementing an expert system with the Certainty Factor (CF) method in diagnosing damage to the Vespa classic from the calculation results of the Certainty Factor (CF) method.